Big Data Analysis to Improve the Competitiveness of Micro, Small, and Medium Enterprises (MSMEs) - Sipra, Sipra (SEAN Institute, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the global economy, but often face challenges in competing in complex markets. Effective data management is key to improving the competitiveness of MSMEs, where Big Data analytics promises great potential. Big Data analytics enables MSMEs to gain in-depth insights into customer behavior, market trends, and better business decisions. However, the implementation of Big Data in MSMEs is not free from challenges such as limited human and technical resources. This study uses the Systematic Literature Review (SLR) method to investigate the implementation of Big Data in improving the competitiveness of MSMEs. The results show that the benefits of Big Data for MSMEs include deeper market understanding, improved business decisions, operational efficiency, personalization of customer experiences, and detection of risks and opportunities. Strategies to overcome these challenges include increasing access to finance, skills development, technology utilization, collaboration, and regulatory compliance. It is also important to pay attention to data security and privacy, with policy implications such as providing access and training, developing policy frameworks, industry and academic collaboration, increasing awareness, and financial support. With proper implementation and adequate policy support, MSMEs can leverage the potential of Big Data to increase their competitiveness in an increasingly complex and dynamic market.